Office Management Literacy and Writing Skills in Supporting the Career Development of Professional Administrative Staff at Senior High School - Hanna Virda Zakiyah; Lutfi Wakhid (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Office management plays a crucial role not only in administrative management but also in the professional development of administrative staff in educational institutions. This study aims to analyze the role of office management in enhancing the competencies and supporting the career development of administrative staff at SMAN 01 Pesanggaran. This study employs a descriptive qualitative approach with the subjects being the school principal, the head of administration, and administrative staff. Data were collected through in-depth interviews, observations, and documentation, then analyzed using an interactive model (reduction, presentation, and drawing of conclusions). Data validity was tested through triangulation of techniques and sources. The results of the study indicate that the POAC functions (planning, organizing, actuating, and controlling) in office management—through clear task allocation, ongoing training, the use of technology, and routine performance evaluations—can enhance the professionalism and career development of administrative staff. The limitations of administrative workload are a barrier to the career development of administrative staff. This provides empirical evidence that office management is not merely technical in nature but constitutes a human resource (HR) development strategy within schools. It demonstrates that the POAC functions can be adapted as strategic work to build career paths for administrative staff, an area that has received insufficient attention in educational management studies. It identifies that workload constraints need to be managed systematically so that competency development is not disrupted—a practical finding for educational institution leaders.